Determining the neural substrate for encoding a memory of human pain and the influence of anxiety - Tseng, M-T; Kong, Y; Eippert, F; Tracey, I (Society for Neuroscience, 2017)
To convert a painful stimulus into a briefly maintainable construct when the painful stimulus is no longer accessible is essential to guide human behavior and avoid dangerous situations. Due to the aversive nature of pain, this encoding process might be influenced by emotional aspects and could thus vary across individuals, but we have yet to understand both the basic underlying neural mechanisms as well as potential inter-individual differences. Using functional magnetic resonance imaging in combination with a delayed-discrimination task in healthy volunteers of both sexes, we discovered that brain regions involved in this working memory encoding process were dissociable according to whether the to-be-remembered stimulus was painful or not, with the medial thalamus and the rostral anterior cingulate cortex encoding painful and the primary somatosensory cortex encoding non-painful stimuli. Encoding of painful stimuli furthermore significantly enhanced functional connectivity between the thalamus and medial prefrontal cortex (mPFC). With regards to emotional aspects influencing encoding processes, we observed that more anxious participants showed significant performance advantages when encoding painful stimuli. Importantly, only during the encoding of pain, the inter-individual differences in anxiety were associated with the strength of coupling between medial thalamus and medial prefrontal cortex, which was furthermore related to activity in the amygdala. These results indicate not only that there is a distinct signature for the encoding of a painful experience in humans, but also that this encoding process involves a strong affective component.SIGNIFICANCE STATEMENTTo convert the sensation of pain into a briefly maintainable construct is essential to guide human behavior and avoid dangerous situations. Although this working memory encoding process is implicitly contained in the majority of studies, the underlying neural mechanisms remain unclear. Using fMRI in a delayed-discrimination task, we found that the encoding of pain engaged the activation of the medial thalamus and the functional connectivity between the thalamus and medial prefrontal cortex. These fMRI data were directly and indirectly related to participants' self-reported trait and state anxiety. Our findings indicate that the mechanisms responsible for the encoding of noxious stimuli differ from those for the encoding of innocuous stimuli, and that these mechanisms are shaped by an individual's anxiety levels.